Limits to male reproductive potential across mating bouts in Drosophila melanogaster. (February 2020) - Douglas, Tracy; Anderson, Raleigh; Saltz, Julia B.
Abstract : Understanding the sources of variation in reproductive fitness is a central goal of sexual selection research. Research investigating factors limiting male reproductive potential typically focus on limited mate availability or mate access. This focus often minimizes the potential relevance of physiological or other limitations on male reproductive potential, in contrast to the emphasis on studying such limitations in females. This gap in knowledge leaves open questions about how variation in male reproductive success emerges across successive mating bouts. Here, we contribute to bridging this gap by examining male reproductive potential across successive matings and across time. To reveal limits to male reproductive potential, and sources of variation in these limits, we measured mating rate and offspring production in Drosophila melanogaster males under conditions in which mate limitation was abrogated and food was abundant. Even under these ideal conditions, we discovered distinct limits to male reproductive potential after just a few mating bouts. After males mated two to five times on a given day, additional matings often resulted in zero progeny. Furthermore, we found nonlinear relationships between the number of females a male mated with and the number of progeny he sired; and these relationships depended on the male's genotype, early life social environment and recent mating experience. These findings suggest that males who obtain more mates do not always sire the most offspring and that males who are highly successful in obtaining mates during one time period may not be able to continue this success on subsequent mating bouts and days. Together, these findings suggest trade-offs between current and future reproduction for males. More broadly, these results highlight how sexual selection studies may be expanded across individuals' lifetimes to develop a fuller picture of how sexual selection shapes variation. Highlights: Limits to reproductive potential are surprisingly understudied in males. We allowed male flies unlimited mating opportunities to reveal reproductive limits. We found that males who mated with more females did not always sire more offspring. Females who received low-quality mates remated rapidly. These findings suggest an upper bound on the reproductive success of any one male.